A la fe por la duda: Una lectura metafísica de la paradoja en “El Hombre Que Fue Jueves” de G.K. Chesterton - Siles González, Ignacio (2005)
The paper examines the metaphysical meanings of paradox in Chesterton’s novel The Man Who Was Thursday. Biographical insights are taken into account to understand the writing process of his novel. Finally, it discusses both Chesterton’s use of paradox as well as his religious and philosophical postures.